Selfishness Of The Main Character In The School For Good And Evil Directed By Paul Feig - Diah Sekar Rini; Adelia Raudatul Rahma; Yanti Rosalinah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study analyzes the selfishness of the main character in the movie of The School for Good and Evil, directed by Paul Feig. The study is limited into (1) Categories of selfishness from Erich Fromm and (2) Cause of selfishness from Ryan W. Carlson. This study is arranged by using qualitative methods.  Finally, the results show there are two categories of the main character’s selfishness namely healthy selfishness and unhealthy selfishness. While, the main character dominates unhealthy selfishness she puts her goals ahead of those of others. Next, the causes of the selfishness in this movie are situation, desire, mind, and expectation.  It reflects that Sophie's selfishness affects her relationships, particularly with her friend, as well as broader social and psychological issues.